Oncogenic mutations of p110α isoform of PI 3-kinase upregulate its protein kinase activity. - Christina M Buchanan (Public Library of Science (PLoS), 2013)
In addition to lipid kinase activity, the class-I PI 3-kinases also function as protein kinases targeting regulatory autophosphorylation sites and exogenous substrates. The latter include a recently identified regulatory phosphorylation of the GM-CSF/IL-3 βc receptor contributing to survival of acute myeloid leukaemia cells. Previous studies suggested differences in the protein kinase activity of the 4 isoforms of class-I PI 3-kinase so we compared the ability of all class-I PI 3-kinases and 2 common oncogenic mutants to autophosphorylate, and to phosphorylate an intracellular fragment of the GM-CSF/IL-3 βc receptor (βic). We find p110α, p110β and p110γ all phosphorylate βic but p110δ is much less effective. The two most common oncogenic mutants of p110α, H1047R and E545K have stronger protein kinase activity than wildtype p110α, both in terms of autophosphorylation and towards βic. Importantly, the lipid kinase activity of the oncogenic mutants is still inhibited by autophosphorylation to a similar extent as wildtype p110α. Previous evidence indicates the protein kinase activity of p110α is Mn(2+) dependent, casting doubt over its role in vivo. However, we show that the oncogenic mutants of p110α plus p110β and p110γ all display significant activity in the presence of Mg(2+). Furthermore we demonstrate that some small molecule inhibitors of p110α lipid kinase activity (PIK-75 and A66) are equally effective against the protein kinase activity, but other inhibitors (e.g. wortmannin and TGX221) show different patterns of inhibition against the lipid and protein kinases activities. These findings have implications for the function of PI 3-kinase, especially in tumours carrying p110α mutations.